Pemanfaatan Media Pembelajaran Sejarah Berbasis Internet di Perguruan Tinggi Abad Ke-21 - Silvy Mei Pradita; Humar Sidik (LITERATUS, 2020)
In the current postmodern era, the internet has transformed into a cutting-edge weapon in various sectors, ranging from industry, art, economy and others. The internet has always played a vital role in maximizing these various sectors. However, what is the real reality in the world of education? Has the internet been fully utilized? Departing from these worries, this research aims to reveal the real reality of the use of the internet at the tertiary level, especially as a medium for learning history. This research itself uses a descriptive qualitative research method. Data collection techniques used in this study were interviews, observation, and document analysis. The interview form used is open and leads to depth of information and is not formal / structured. The goal is to explore the information that is researched further, complete, and in depth. Data analysis in the study took place simultaneously with the data collection process. Among them through data reduction, data presentation, and verification. The results showed that in 21st century learning, the internet has an important role if teachers can maximize its use, because with the internet students are able to dig deeper into existing information, especially now that there are so many historical journal portals that are opened online and accessed for free. Furthermore, the use of the internet can also be applied in a learning system, for example by using blended learning